2020
DOI: 10.1002/jmri.27056
|View full text |Cite
|
Sign up to set email alerts
|

MRI vs. CT for the Detection of Liver Metastases in Patients With Pancreatic Carcinoma: A Comparative Diagnostic Test Accuracy Systematic Review and Meta‐Analysis

Abstract: Background: The detection of liver metastases is important for pancreatic cancer curative treatment eligibility. The data suggest that magnetic resonance imaging (MRI) is more sensitive than computed tomography (CT) for the diagnosis of pancreatic cancer liver metastases. However, MRI is not currently recommended in multiple published guidelines. Purpose: To perform a comparative diagnostic test accuracy systematic review and meta-analysis comparing CT and MRI for pancreatic cancer liver metastases detection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 38 publications
1
25
1
Order By: Relevance
“…Standard of care imaging techniques for PDAC include transabdominal ultrasonography (2), computed tomography (3), magnetic resonance imaging (4,5) and endoscopic ultrasonography (6), with contrast enhanced CT considered the gold standard for TNM staging in pre-operative and follow-up settings (7,8). Positron Emission Tomography with 18 F-Fluorodeoxyglucose (FDG) is not part of the clinical routine, but is sensitive for initial TNM-staging (9), evaluation of treatment response (10) and detection of recurrence (11).…”
Section: Introductionmentioning
confidence: 99%
“…Standard of care imaging techniques for PDAC include transabdominal ultrasonography (2), computed tomography (3), magnetic resonance imaging (4,5) and endoscopic ultrasonography (6), with contrast enhanced CT considered the gold standard for TNM staging in pre-operative and follow-up settings (7,8). Positron Emission Tomography with 18 F-Fluorodeoxyglucose (FDG) is not part of the clinical routine, but is sensitive for initial TNM-staging (9), evaluation of treatment response (10) and detection of recurrence (11).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the good diagnostic performance of MRI for liver metastases, the benefits of MRI remain unclear, mostly because of low level of evidence, heterogeneity, and bias in the performed studies. Two recently published meta-analyses have suggested the results should be confirmed by performing a well-designed and sufficiently powered study directly comparing liver CT and MRI in the same cohort [37,38].…”
Section: Discussionmentioning
confidence: 92%
“…Ito et al demonstrated that a significant predictor of LM was the identification of possible lesions on EOB-MRI, while other preoperative clinical factors, such as tumor markers and CECT findings were not predictive of LM [ 10 ]. Recently, a systematic review [ 23 ] reported that MRI was more sensitive than CT in detecting pancreatic cancer LM. This study supports our results; however, not all reviewed studies compared EOB-MRI with CECT in patients with PDAC while only two included studies performed MRI with a liver-specific agent in PDAC.…”
Section: Discussionmentioning
confidence: 99%